Patient and public involvement in developing and validating an instrument for assessing the scaling potential of innovations in health and social services: A consensus study - Roberta de Carvalho Corôa; Ali Ben Charif; Claude Bernard Uwizeye; Florence Lizotte; Amédé Gogovor; Robert K.D. McLean; Andrew Milat; Léonel Philibert; Louisa Blair; Kathy Kastner; Jean-Sébastien Renaud; France Légaré (PLoS ONE, 2025)
Background Before proven health innovations are scaled, an assessment of their scaling potential can save resources and assure quality at scale. Involving the beneficiaries of scaling is necessary for it to be effective and relevant. We aimed to develop, with patient and public involvement (PPI), an instrument for assessing the scalability of innovations in health and social services and to establish content validity. Methods We conducted a multiphase study based on the Integrated Knowledge Translation approach and the Montreal Model for PPI. A steering committee provided feedback throughout the project. Informed by a systematic review, the research team and steering committee selected promising items for inclusion in the instrument. In a two-round online Delphi process, patients and public representatives and other expert panellists reached consensus on the relevance, clarity and necessity of each item. Finally, with a patient partner and two scaling teams we developed the instrument and a manual. Results The steering committee consisted of a patient partner, an expert in health measures and two policymakers who were experts in scaling. Based on the systematic review, we retained 43 items covering 12 domains. Two new items related to PPI and sex- and gender-sensitive scaling were validated by the committee. A 24-member Delphi panel assessed the resulting 45 items for content validity. Patients and public representatives constituted 29.1% of the panel and researchers 25%. Fourteen items were excluded for not reaching content validity thresholds. The final selection included three items added by panellists (consideration of national and local legislation, disadvantages of not scaling, and equity). Despite a low score, an item on sex and gender was retained as being essential for redressing consequences of inequities in health research. Conclusion The final tool, the Innovation Scalability Self-administered Questionnaire (ISSaQ 4.0), includes 37 items across 12 domains and is available in French and English.